The incidence, prevalence, and health burden of forearm fractures in China from 1992 to 2021 and forecasts for 2036 - Zeng, Yuan; Hu, Minhua; Zhang, Zhiming; Chen, Jiayi; Luan, Feifan; Wu, ZhiSen; Zheng, Chenxiao (Frontiers in Public Health, 2025)
BackgroundForearm fractures (Fracture of radius and/or ulna) are common worldwide and constitute a significant public-health burden. There is limited epidemiological data on radius and/or ulna fractures in the Chinese population. Using data from the Global Burden of Disease (GBD) 2021 study, this research reports the epidemiology and disease burden of forearm fractures in China, as well as projected trends for the next 15 years.MethodsData on the incidence, prevalence, and years lived with disability (YLDs) for Fractures of the radius and ulna in mainland China from 1992 to 2021 were obtained from the 2021 GBD database. Joinpoint regression analysis was used to analyze epidemiological trends in incidence, prevalence, and age-standardized rates (ASIR, ASPR, ASYR) over the period from 1992 to 2021. The Bayesian Age-Period-Cohort (BAPC) model was employed to project trends in incidence and YLDs for radius and/or ulna fractures in mainland China from 2022 to 2036.ResultsIn 2021, there were 5,790,636 radius and/or ulna fractures in China, with 2,724,178 in males and 3,066,459 in females. The age-standardized incidence rate (ASIR) for radius and/or ulna fractures was 404.52 per 100,000, with 375.83 in males and 430.87 in females. The age-standardized years of disability (ASYR) was 2.55 years per 100,000, with 2.22 years in males and 2.82 years in females. From 1990 to 2021, both the ASIR and ASYR increased, with an average annual percent change (EAPC) of 0.09. The incidence of radius and/or ulna fractures peaked in males at ages 30–34, and in females at ages 50–54 and 65–69. Joinpoint regression analysis revealed a decline in incidence and prevalence from 2001 to 2005, followed by a significant increase from 2011 to 2021. Projected data suggests that the ASIR for radius and/or ulna fractures in males will rise from 369 per 100,000 to 374 per 100,000 from 2022 to 2029. This will be followed by a slight decline from 373 per 100,000 in 2030 to 368 per 100,000 in 2036, while the rate in females is expected to steadily increase from 427 per 100,000 in 2022 to 502 per 100,000 in 2036.ConclusionIn 2021, an estimated 5,790,636 radius and/or ulna fractures occurred in China. Prevalence and disability rates were higher among women than among men. After a decline between 2001 and 2005, the incidence, prevalence, and disability burden of these fractures rose sharply from 2011 to 2021. Projections indicate that incidence in men will fall slightly after 2030, whereas it will continue to rise in women. These findings provide critical evidence for shaping public-health policy, designing fracture-prevention programmes, and allocating healthcare resources in China.